Glass ceilings or glass doors? Wage disparity within and between firms - Krishna Pendakur; Simon Woodcock (Institute for the Study of Labor (IZA), 2009)
We investigate whether immigrant and minority workers' poor access to high-wage jobs - that is, glass ceilings - is attributable to poor access to jobs in high-wage firms, a phenomenon we call glass doors. Our analysis uses linked employer-employee data to measure mean- and quantile-wage differentials of immigrants and ethnic minorities, both within and across firms. We find that glass ceilings exist for some immigrant groups, and that they are driven in large measure by glass doors. For some immigrant groups, the sorting of these workers across firms accounts for as much as half of the economy-wide wage disparity they face.
Keywords: J15; J71; J31; 330; Glass ceilings; wage differentials; immigration; visible minorities; quantile regression; linked employer-employee data; Arbeitsmarktdiskriminierung; Lohnstruktur; Migranten; Ethnische Gruppe; Schätzung; Kanada